Фотопровідність кремнію в умовах магнітного впливу - Макара, В.А.; Стебленко, Л.П.; Подолян, А.О.; Курилюк, А.М.; Кобзар, Ю.Л.; Науменко, С.М. (Видавничий дім "Академперіодика" НАН України, 2008)
It is shown that the action of magnetic fields (MF) of different nature (constant and variable MF and a microwave superhigh-frequency field) changes the relaxation kinetics of photoconductivity (PC) in silicon crystals. For an explanation of the obtained results, the mechanism, according to which differences in the relaxation times of PC are related to structural changes in the surface layer of Si that are stimulated by the magnetic influence, is offered.